2016
DOI: 10.1016/j.physletb.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The Coulomb interaction in Helium-3: Interplay of strong short-range and weak long-range potentials

Abstract: Quantum chromodynamics and the electroweak theory at low energies are prominent instances of the combination of a short-range and a long-range interaction. For the description of light nuclei, the large nucleon-nucleon scattering lengths produced by the strong interaction, and the reduction of the weak interaction to the Coulomb potential, play a crucial role. Helium-3 is the first bound nucleus comprised of more than one proton in which this combination of forces can be studied.We demonstrate a proper renorma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
1
12
1
Order By: Relevance
“…We examine how the fitted values of the coefficients vary with the width of the Gaussian regulator, σ, and exclude the region where these coefficients start to become "unnaturally" large. This is contrast to the recent work by Kirscher and Gazit [31] who use a similar potential to ours but with cut-offs corresponding to σ in the range 0.08 to 0.25 fm.…”
Section: Pionless Eftcontrasting
confidence: 97%
“…We examine how the fitted values of the coefficients vary with the width of the Gaussian regulator, σ, and exclude the region where these coefficients start to become "unnaturally" large. This is contrast to the recent work by Kirscher and Gazit [31] who use a similar potential to ours but with cut-offs corresponding to σ in the range 0.08 to 0.25 fm.…”
Section: Pionless Eftcontrasting
confidence: 97%
“…Based on studying the regulator (cutoff) dependence of the amplitude, it was realized that in the presence of nonperturbative Coulomb effects an isospin breaking three-nucleon force is required to ensure renormalization at next-to-leading order (NLO) [24,45]. While another calculation [46] does not see the need to include such a term, Ref. [25] showed that in part this three-body force is related to a two-body divergence in the pp sector, and that the theory can be rearranged in such a way that all Coulomb effects in the 3 He bound state are included in perturbation theory.…”
Section: Introductionmentioning
confidence: 99%
“…[30] with a different scheme, and in Ref. [12] with the same formalism as employed in this work. Within our scheme, we find the divergence only by splitting the LEC in the pp channel as shown.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion of this section, we note that the orderings are unaffected by the regularized Coulomb interaction and consequently should be characteristics of the strong interaction. (12) In Table III we present the evolution of the nuclear magnetic moments in EFT(π ). The values of shell-model approximation yield the magnetic moment as the sum of the single particle contributions with appropriate spin orientations.…”
Section: Charge Radiimentioning
confidence: 99%